Self-assembling human heart organoids for the modeling of cardiac development and congenital heart disease - Yonatan R. Lewis-Israeli (Nature Portfolio, 2021)
There is a pressing need to develop representative organ-like platforms recapitulating complex in vivo phenotypes to study human development and disease in vitro. Here the authors present a method to generate human heart organoids by self-assembly using pluripotent stem cells, compare these to age-matched fetal cardiac tissues and recreate a model of pregestational diabetes.